Mask Use with Spacers/Valved Holding Chambers and Metered Dose Inhalers among Children with Asthma - Volerman, Anna (Ann Am Thorac Soc, 2021)
Inhaler misuse is highly prevalent and associated with high morbidity and costs. For metered dose inhalers, proper use can be supported with devices such as spacers/valved holding chambers (VHCs) and masks to effectively deliver inhaled medication to the lungs. However, guidelines are vague about which children with asthma should use spacers/VHCs with masks to deliver medication from metered dose inhalers as well as when they should transition to spacers/VHCs with mouthpieces. In this paper, we provide a focused review of the evidence for mask use, highlighting unclear and conflicting information in guidelines and studies. We synthesize the differences in recommendations and practice. Based on these findings, we call for future research to determine the appropriate age and necessary skills for transitioning children from using metered dose inhalers with spacers/VHCs and masks to using spacers/VHCs and mouthpieces. Guidelines about mask use should be standardized to help ensure optimal medical delivery for patients, provide consistent inhaler prescriptions and education across settings, and support team-based care to help lower pediatric asthma morbidity and costs.